2019
DOI: 10.1002/ehf2.12393
|View full text |Cite
|
Sign up to set email alerts
|

Differences in nutritional status and activities of daily living and mobility in elderly hospitalized patients with heart failure

Abstract: Aims This study aims to examine the effect of differences in nutritional status on activities of daily living (ADL) and mobility recovery of hospitalized elderly patients with heart failure (HF). Methods and results From among 377 consecutive HF patients who underwent rehabilitation at one acute‐care hospital from January 2013 to August 2015, those who were aged ≥ 65 years could walk with assistance before hospitalization and who were hospitalized for the first time wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…From previous studies, ADL and nutrition of elderly HF patients are known independent factors of readmission [9,14]. However, the relation between ADL and nutrition has been only partially reported [36], and its causal relationship is unknown. In contrast, some studies reported that ADL in hospitalized HF patients with poor nutritional status is reduced, perhaps due to a decrease in muscle mass and function [37,38].…”
Section: Relation Between Adl Gnri and The Rate Of Readmissionmentioning
confidence: 99%
“…From previous studies, ADL and nutrition of elderly HF patients are known independent factors of readmission [9,14]. However, the relation between ADL and nutrition has been only partially reported [36], and its causal relationship is unknown. In contrast, some studies reported that ADL in hospitalized HF patients with poor nutritional status is reduced, perhaps due to a decrease in muscle mass and function [37,38].…”
Section: Relation Between Adl Gnri and The Rate Of Readmissionmentioning
confidence: 99%
“…The 3.0-kg improvement in maximal grip strength, in our case, was clinically meaningful because a 1-kg improvement in grip strength is associated with a 5% improvement in all-cause mortality [22]. The reason for the improvement of physical function in this patient was the high rate of rehabilitation because there were few instances of refusal or difficulty in rehabilitation, and her nutritional status improved because the anorexia improved and the amount of food consumed increased [23] (Fig. 2).…”
Section: Discussionmentioning
confidence: 52%
“…Contributing elements to the deleterious changes in body composition in patients with cardiac cachexia are anorexia, malnutrition, intestinal congestion [144], and an inflammatory cytokine storm, which have also been described as common complications in severe HF [145,146]. High serum levels of adiponectin [147], a protein involved in the cellular energy control of several tissues, have been found in HF patients with cachexia, unrelated to their body mass index [148].…”
Section: Sarcopenia In Cardiac Cachexiamentioning
confidence: 99%